Analysis of smoke movement in the Hsuehshan tunnel fire. (February 2019) - Chen, Yu-Jen; Shu, Chi-Min; Ho, San-Ping; Kung, Hsiang-Cheng; Chien, Shen-Wen; Ho, Hsin-Hsiu; Hsu, Wen-Sheng
Abstract: In 2012, a serious fire accident occurred in the Hsuehshan southbound road tunnel, which resulted in two fire fatalities and 34 injuries. A pickup truck was hit by a bus from behind; gasoline leaked from the bus and started the fire. Smoke was diverted from the southbound tunnel into the service tunnel and the northbound tunnel via two connection tunnels. Fire dynamics simulator (FDS) software was used to simulate the smoke movement in the 13 km long southbound road tunnel, employing more than 21 million computational cells. The heat release rate curve used in the simulation was based on a single bus fire which reached a maximum value of 30 MW. The smoke front movement obtained from the computer simulation was compared with that determined from the closed circuit TV (CCTV) recordings, and the agreement between the simulation results and CCTV recordings was sound. The critical velocity for controlling backlayering of a 30 MW bus fire was also determined from simulation, which agreed well with the value estimated from empirical correlations of model experiments. This research showed that during a fire, doors to connection tunnels should close automatically, and the service tunnel should only be used for emergency rescue purpose, instead of evacuation of people.